2021
DOI: 10.3390/pharmaceutics13040507
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Predictive Dissolution Methodology (iPD Methodology) with a BCS Class IIb Drug Can Predict the In Vivo Bioequivalence Results: Etoricoxib Products

Abstract: The purpose of this study was to predict in vivo performance of three oral products of Etoricoxib (Arcoxia® as reference and two generic formulations in development) by conducting in vivo predictive dissolution with GIS (Gastro Intestinal Simulator) and computational analysis. Those predictions were compared with the results from previous bioequivalence (BE) human studies. Product dissolution studies were performed using a computer-controlled multicompartmental dissolution device (GIS) equipped with three diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The dissolution media, initial volumes, and secretion rates are described in Table 2. The transfer rate from the stomach to the duodenum was set as a first-order kinetic process with a gastric half-life of 8 min, in accordance with human data [11,12]. The volume of the stomach was decreasing from 300 mL to 10 mL.…”
Section: Dissolution Experiments In Gismentioning
confidence: 99%
See 1 more Smart Citation
“…The dissolution media, initial volumes, and secretion rates are described in Table 2. The transfer rate from the stomach to the duodenum was set as a first-order kinetic process with a gastric half-life of 8 min, in accordance with human data [11,12]. The volume of the stomach was decreasing from 300 mL to 10 mL.…”
Section: Dissolution Experiments In Gismentioning
confidence: 99%
“…The final permeability values are displayed in Table 7. Fsys 0.39 0.39 0.39 [11] k t (min −1 ) 0.0056 0.0056 0.0056 [15] tcut (min) 600 360 600 [11] k pre_s (min The gastric emptying times were shortened (from 15 to 13 min) for the VALS_Supra/ HCTZ BE formulation. These gastric emptying times were based on previous human intubation studies (13 min) with a 2 min delay in the formulation containing more sorbitol, based on the AUC and C max ratio differences for the HCTZ in both test products.…”
Section: Parameter (Units) Valuementioning
confidence: 99%
“…[23][24][25] In addition, it is necessary to control the dissolution of poorly soluble APIs because the dissolution process in the gastrointestinal tract is critical for BE. [26][27][28] We initially expected that products with poorly soluble APIs would be more dissimilar from those with highly soluble APIs. However, our study indicated that API solubility was not associated with changes in the dissolution profiles of the marketed products (Fig.…”
Section: (B)) a Product Listed In The Jp-orangementioning
confidence: 99%
“…Etoricoxib is a lipophilic (logP = 2.8), and weakly basic drug (pKa = 5.0), showing low and pH-dependent aqueous solubility. It is classified as a BCS (biopharmaceutics classification system) class II compound [ 4 ].…”
Section: Introductionmentioning
confidence: 99%